Pengembangan E-LKPD Bermuatan Problem Based Learning (PBL) Berbasis Website Liveworksheets Pada Pembelajaran Geografi SMA - Anggun Purborini; Astutik, Sri; Ana Susiati; Fahmi Arif Kurnianto; Bejo Apriyanto (JPIG (Jurnal Pendidikan dan Ilmu Geografi), 2025)
The development of 21st century learning is always associated with advances in Information and Communication Technology used in learning activities. Therefore, teaching material products are needed that are in line with the application of 21st century learning. The aim of this research is to develop electronic student worksheets teaching materials containing Problem Based Learning based on live worksheet websites in geography learning. Using a type of development research or R&D (Research and Development) with the ADDIE (Analyze, Design, Development, Implementation, and Evaluation) development model. The research results obtained show that electronic student worksheets containing Problem Based Learning based on the live worksheet website was declared very valid by expert validators with a total percentage result of 92.77%. The e-LKPD product developed also produced good responses from students with a total percentage of 82.75%. The electronic student worksheets product developed is considered capable of improving student learning outcomes as proven by obtaining a total percentage of 91.60% of students who obtained a score above the minimum completeness.